An Efficient Electrochemical Tanks-in-Series Model for Lithium Sulfur Batteries. Issue 16 (3rd December 2020) - Parke, Caitlin D.; Subramaniam, Akshay; Kolluri, Suryanarayana; Schwartz, Daniel T.; Subramanian, Venkat R.
Abstract : This article applies and efficiently implements the Tanks-in-Series methodology ( J. Electrochem. Soc., 167, 013534 (2020)) to generate a computationally efficient electrochemical model for Lithium-Sulfur batteries. The original Tank model approach for Lithium-ion batteries is modified to account for porosity changes with time. In addition, an exponential scaling method is introduced that enables efficient simulation of the model equations to address the wide range of time constants present for different reactions in the Lithium-Sulfur system. The Tank Model achieves acceptable voltage error even for transport-limited discharged conditions. Predictions of internal electrochemical variables are examined, and electrochemical implications of the approximations discussed. This suggests significant potential for real-time applications such as optimal charging, cell-balancing, and estimation, and represents a step forward in efforts to incorporate detailed electrochemical models in advanced Battery Management Systems for Lithium-Sulfur batteries.